Nucleosides, XLVII. Syntheses, Reactions and Properties of 6- and 7-p-Bromophenyllumazine N-1-Nucleosides - Al-Masoudi Najim A. L.; Pfleiderer Wolfgang (Pteridines, 1990)
Glycosylation of 6-(2) and 7-p-bromophenyllumazine (3) by the silyl method using 1-O-acetyl-2.3 ,5-tri-O-benzoyl-β-D-ribofuranose (6) and trimethylsilyl trifluoromethanesulfonate as catalyst proceeded regioselectively in high yields to the N-1 nucleosides (7, 11). Thiations by P4S10 or Lawesson’s reagent led to the corresponding 4-thiolumazine ribosides (9, 13). Deblocking to the free nucleosides (8, 10, 12. 14) worked best with K2CO3, in MeOH. Treatment of 9 and 13 respectively by methanolic NH3 afforded debenzoylation and di splacement of the thio-function to give the corresponding isopterin N-1 ribofuranosides (15.16). 2,2ʹ-Anhydro- nucleoside formation was achieved with 8 and 10 respectively to give 17 and 18, which formed on acid hydrolysis the 6- and 7-substituted l-~-D-arabinofuranosyl-lumazines 19 and 20.